PERANCANGAN MOTION GRAPHIC IKLAN LAYANAN MASYARAKAT (ILM) TENTANG PRILAKU MENYIMPANG LESBIAN, GAY, BISEKSUAL DAN TRANSGENDER (LGBT) PADA MASYARAKAT - MUTHIA HUMAIRAH, Drs. Syafwan, M.Si, Riri Trinanda, S.Pd., M.Sn (DEKAVE : Jurnal Desain Komunikasi Visual, 2015)
The globalization that causes changes in various parts of the world have an impact on the social and cultural values in society. One of them is deviant behavior LGBT. LGBT is the phenomenon of sexual deviation that occurs in the middle of a society that is now growing quite rapidly until well into the realm of social, cultural, political, health education and so on. From this, it made a design ILM, to address the prevention of dissemination of this deviant behavior by using motion graphic media. This media is made in the duration of 56 seconds and is considered more effective in addition supported by the display form of pictures / illustrations, video, animation and audio that can directly be understood by the target audience. This work is also flexible to be aired on television, self tv, youtube, internet etc. Design method used is 5W 1H, the method used to answer questions, WHO (who), says what (say what), to Whom (to whom), why, when and How (How).Kata kunci : Motion Graphic, LGBT, Iklan Layanan Masyarakat.